SYED MUHAMMAD NAQUIB AL-ATTAS’ IDEAS ON THE ISLAMIZATION OF KNOWLEDGE AND ITS RELEVANCE WITH ISLAMIC EDUCATION IN INDONESIA - Kosim, Muhammad; Kustati, Martin; Murkilim, Murkilim (State Islamic University North Sumatra, 2020)
Abstract: This article discusses on Syed Muhammad Naquib al-Attas’s thoughts on the Islamization of Knowledge and analyzes its relevance to the development of Islamic education in Indonesia. A library research was employed by collecting relevant papers and writings. To interpret literatures, a hermeneutic approach was used where the data taken from content analysis. The study showed that the main thought of Naquib al-Attas was that all knowledge comes from Allah SWT. Meanwhile, the development of Western science tends to be secular. The Islamization of knowledge must be carried out in the Islamic education system by releasing knowledge from various interpretations based on secular ideology, meanings and expressions. The idea has relevance to the development of Islamic education as an effort to overcome the dichotomy paradigm of science in Indonesia.Keywords: Islamization of knowledge, al-Attas, Indonesia’s Islamic education